2020
DOI: 10.1111/eci.13404
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of neutrophil‐lymphocyte ratio in COVID‐19

Abstract: Background The clinical presentation of COVID‐19 ranges from a mild, self‐limiting disease, to multiple organ failure and death. Most severe COVID‐19 cases present low lymphocytes counts and high leukocytes counts, and accumulated evidence suggests that in a subgroup of patients presenting severe COVID‐19, there may be a hyperinflammatory response driving a severe hypercytokinaemia which may be, at least in part, signalling the presence of an underlying endothelial dysfunction. In this context, available data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 33 publications
10
103
0
7
Order By: Relevance
“…Neutrophil and lymphocyte ratio (NLR) has been proposed as a prognostic marker of severity in various chronic inflammatory diseases, including cardiovascular diseases and oncological processes 17 .…”
Section: No Growthmentioning
confidence: 99%
“…Neutrophil and lymphocyte ratio (NLR) has been proposed as a prognostic marker of severity in various chronic inflammatory diseases, including cardiovascular diseases and oncological processes 17 .…”
Section: No Growthmentioning
confidence: 99%
“…Neuropilin (NRP1), a cell surface receptor expressed in respiratory and olfactory epithelium, can also facilitate SARS-CoV-2 cellular entry 11 . Patients with COVID-19 infection often have lymphopenia in association with high neutrophil and platelet counts, parameters which may give prognostic indication 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A multi-center retrospective study also reported the NLR was an independent risk factor for patient survivals in H7N9 pneumonia [4]. A retrospective observational study found that the NLR was an easily measurable, available, cost-effective and reliable parameter, which continuous monitoring may be useful for the diagnosis and treatment of COVID-19 [19]. Taken together, these results reveal that the NLR in hematological examination is an important clinical parameter for the prediction of patient prognosis in the pneumonia caused by viral infections, including the in uenza and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen was later identi ed to be a previously unknown beta coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1]. The World Health Organization (WHO) denominated the new disease as coronavirus disease 2019 (COVID- 19) in February and declared COVID-19 outbreak a pandemic in March, 2020. Until the October 1, 2020, more than 30 million con rmed COVID-19 cases have been reported globally, with more than 1,000,000 patient deaths.…”
Section: Introductionmentioning
confidence: 99%